Antihyperalgesic Effect of the GABAA Ligand Clobazam in a Neuropathic Pain Model in Mice: A Pharmacokinetic–Pharmacodynamic Study. (14th November 2012) - Besson, Marie; Daali, Youssef; Di Lio, Alessandra; Dayer, Pierre; Zeilhofer, Hanns Ulrich; Desmeules, Jules
Abstract Facilitation of spinal GABAergic inhibition with benzodiazepines (BZDs) reverses pain sensitization in animals; however, the use of BZDs in man is limited by their sedative effect. The antihyperalgesic effects of GABAA agonists are mediated by GABAA receptors containing α2 subunits, whereas sedation is linked to α1 subunit‐containing receptors. α2 and α3 selective GABAA receptor modulators have been tested in animals but are not yet available for use in human beings. Clobazam is a 1, 5‐BZD, which exhibits less cognitive side effects than other benzodiazepines. Here, we studied its antihyperalgesic effects in a mouse model of neuropathic pain. Clobazam showed a dose‐dependent antihyperalgesic effect in the chronic constriction injury (CCI) model of neuropathic pain, peaking at 1 hr after administration and lasting for 4 hr with no relevant sedation at a dose of 3 mg/kg. At higher doses, the antihyperalgesic effect was stronger, but sedation became significant. The blood and brain kinetics of clobazam were linear over the range of doses tested with a short half‐life of the parent compound and a ready penetration of the blood–brain barrier. Clobazam blood concentrations decreased rapidly, falling below the limit of detection at 120 min. after drug application. Its main metabolite, N‐desmethyl‐clobazam, showed more delayed and prolonged pharmacokinetics, partly explaining why antihyperalgesia persisted when clobazam was no longer detectable in the blood. Considering its therapeutic margin and its pharmacokinetic properties, clobazam would be a valuable compound to assess the role of the GABAergic pathway in pain transmission in human beings.